Toward Enhancing Research with the Social Information Processing Approach to Job Design - Blau, Gary; Katerberg, Ralph (Academy of Management Review, 1982)
This paper suggests and discusses fundamental content and process questions within the social information processing approach in need of research. Evidence from existing social cue experiments is critically analyzed, and relevant insights from related fields of research are reviewed. These content and process questions must be addressed by researchers in order not only to provide for a fuller understanding of the social information processing approach itself, but also to understand the conditions necessary to maximize the effectiveness of job design programs.